Concern for severe COVID-19 disease during the initial two years of pandemic in a rural South African community: A population-based study - Armstrong Dzomba; Palesa Mataboge; Nicole K. Kelly; Kelechi Elizabeth Oladimeji; Carren Ginsburg; Bianca Moffett; Chodziwadziwa Kabudula; Kimberley Gutu; Audrey Pettifor; Francesc Xavier Gómez-Olivé; Kathleen Kahn (PLoS ONE, 2025)
Background Globally, as of December 2023, over 700 million cases of COVID-19 were confirmed since the initial outbreak late in 2019, claiming around 7 million lives and fuelling widespread fear and anxiety. However, prospective patient-data are unavailable to assess individuals’ perceptions of risk of severe COVID-19 illness, which may imply actual disease severity and inform risk perception for future epidemics. Methods We surveyed 1701 adults about their concern for severe COVID-19 disease using a population-based survey of rural South Africans. The initial telephonic survey was conducted between August-October 2020 with a follow-up survey conducted between August-October 2021. Multinomial logistic regression was used to investigate predictors of perceived COVID-19 illness severity (low, medium, or high) controlling for measured confounders. Results The prevalence of concern for COVID-19 illness severity in 2020 was 28.7% low, 26.8% moderate and 44.5% severe, with corresponding levels in 2021 of 42%, 31.8% and 29.2%, respectively. Although older age was associated with a lower odds of COVID-19 concern [50–59 years (aOR=0.54, 95% CI: 0.38–0.75)], [≥60 years (aOR=0.41,95% CI: 0.41–0.57)], adults having ≥1 chronic conditions (aOR=1.38,1.00–1.89) or residing outside of the study community (aOR=1.29,1.01–1.65) were more likely to experience moderate and high concern for illness severity, respectively. Conclusions Understanding presumptive COVID-19 disease severity may help disentangle various underlying mechanisms behind personal risk assessment. This may inform current thinking and practice of public health emergency medicine in managing emerging and re-emerging respiratory diseases with pandemic potential such as hPMV.